Multicomponent adsorption dynamics in the recovery of acetic and lactic acids using stratified fixed-beds - Naidu, Haripriya (Kansas State University, 2020)
Industrial acetic acid production based on anaerobic fermentation technology is not economically viable at present due to the low efficiency and high cost of product recovery by adsorption or extraction at neutral pH conditions. With the recent advances in fermentation technology to produce organic acids at low pH conditions, a detailed study on the adsorption equilibria, kinetics, and dynamics at these conditions is necessary for the design of an efficient recovery scheme. Adsorption equilibria and kinetics of acetic acid at low pH conditions on granular activated carbon (GAC) and weak base resins were studied using batch experiments. A simple nonlinear estimation method and approximations to analytical solutions of adsorption kinetic equations were developed to determine isotherm constants and kinetic parameters respectively. Weak base resins show higher adsorption capacities for the uptake of acetic acid compared to GAC. Multicomponent sorption equilibria of acetic and lactic acids were determined using the Ideal Adsorbed Solution Theory (IAST) model, and extended Langmuir and modified extended Langmuir models. The adsorption of acetic acid is shown to be controlled by both external mass transfer and intraparticle diffusion resistances in GAC and by intraparticle diffusion resistance alone in the weak base resins. The estimated transport coefficients are shown to predict batch adsorption kinetic data well. Adsorption dynamics studies were conducted using single and multicomponent solutions of acetic and lactic acids in fixed-bed adsorbers of different configurations. These studies were conducted to examine potential enhancements to bed capacity utilization and thereby the overall efficiency of the recovery process. Five different configurations, namely, a conventional cylindrical adsorber (CCA), and a tapered bed adsorber with single adsorbent particle size, a stratified cylindrical adsorber with particle sizes increasing in the direction of flow (SCA), a reverse stratified cylindrical adsorber (RSCA), and a reverse stratified convergent tapered adsorber (RSTA) were studied in this research. A general rate model that considers axial dispersion, external mass transfer, pore diffusion, and nonlinear isotherm was developed to predict sorption dynamics in single and multicomponent systems. Model predictions were in good agreement with experimental data. The adsorption dynamics and breakthrough curves for acetic acid were similar in cylindrical and tapered beds when a single adsorbent particle size was used. The solute front becomes dispersive in the SCA and sharpens in the RSTA. Among the different configurations examined, RSTA gave the maximum bed capacity utilization which is 18.4% higher than that obtained using SCA. Multicomponent sorption dynamics of acetic and lactic acids on weak base resins were conducted in RSTA at pH 2.8 and 4.8. At pH 2.8, acetic acid eluted first, while at pH 4.8 lactic acid eluted first. Sensitivity analysis has shown that to achieve 90% bed capacity utilization, two column lengths or double the quantity of adsorbent will be required in the case of SCA when compared to RSTA. The model presented will be useful in the selection of optimum operating conditions to obtain maximum bed capacity utilization, and thereby enhance the economics of the recovery of organic acids from fermentations.
Keywords: Multicomponent adsorption dynamics; Layered beds; Adsorption; Acetic acid; Lactic acid; Tapered bed